Implementasi Kurikulum Merdeka Dalam Kegiatan Pembelajaran Pendidikan Islam - M. Willy Wildan Maulana; Idzi Layyinati; Subhan Adi Santoso (DIDAKTIKA, 2025)
The Independent Curriculum gives educators the freedom to create quality learning that suits students' needs and learning environment. Teachers have the freedom to choose various teaching tools so that learning can be tailored to the learning needs and interests of students. The curriculum is only concerned with the learning outcomes that students are expected to achieve. This research uses a Descriptive-Qualitative paradigm approach, as a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. According to them, this approach is directed at the setting and the individual in a holistic (whole) manner. This research was conducted at Madrasah Tsanawiyah Islahiyah Kuro Karang Binangun Lamongan. The research findings that have been obtained are Islamic Religious Education Learning Planning, Implementation of Islamic Religious Education Learning, Evaluation of Islamic Religious Education Learning.